The Mediating Role of Capital Intensity Between Executive Character and CEO Duality in Tax Avoidance - Ubaidillah, Moh (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
The largest source of Indonesian government revenue is tax when compared to other sector sources. However, there are still many companies doing tax avoidance because there are tax law loopholes, so that tax revenue is not optimal. This study aims to determine the effect of executive character and CEO duality on tax avoidance with capital intensity as a mediating variable. This research was conducted in mining companies listed on the Indonesian stock exchange in 2018-2022. The research sample was 52 companies with purposive sampling method. The analysis method used is multiple linear regression analysis. The stages of data analysis in this study are classical assumptions to see the feasibility of data, t tests and sobel tests to determine the effect of independent variables on the dependent variable and influence as a moderating variable. The results of this study are CEO duality and capital intensity partially have a positive and insignificant effect on tax avoidance. Executive character partially has a positive and significant effect on tax avoidance. Capital intensity cannot mediate CEO duality and executive character on tax avoidance.